Heating, ventilating, and air conditioning : analysis and design - McQuiston, Faye C. (Faye Clem), 1928-; Parker, Jerald D. (New York ; Chichester : John Wiley and Sons, 1994)
Introduction. Air-conditioning systems. Moist air properties and conditioning processes. Indoor air quality-comfort and health. Heat transmission in building structures. Solar radiation. Space heat load. The cooling load. The cooling load. Energy calculations. Flow, pumps, and piping design...
Keywords: Heating; Ventilation; Air conditioning; Heating; Ventilation; Air conditioning